2014
DOI: 10.3390/ph7121069
|View full text |Cite
|
Sign up to set email alerts
|

Allosteric Modulation of GABAA Receptors by an Anilino Enaminone in an Olfactory Center of the Mouse Brain

Abstract: In an ongoing effort to identify novel drugs that can be used as neurotherapeutic compounds, we have focused on anilino enaminones as potential anticonvulsant agents. Enaminones are organic compounds containing a conjugated system of an amine, an alkene and a ketone. Here, we review the effects of a small library of anilino enaminones on neuronal activity. Our experimental approach employs an olfactory bulb brain slice preparation using whole-cell patch-clamp recording from mitral cells in the main olfactory b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 72 publications
0
11
0
Order By: Relevance
“…However, neither the Open Journal of Physical Chemistry mechanism of the anticonvulsant activities nor the molecular target(s) of these active enaminones have been fully determined or known. There is some evidence that the anticonvulsant activities of these enaminones appear to act through two modes of action: inhibition of sodium channels and via a GAB Aergic pathway [7] [8]. Recent electrophysiology studies have shown that some of a group of newly synthesized 6 Hz active anticonvulsant fluorinated N-benzamide enaminone analogs exhibit inhibition of Na v channels [14].…”
Section: Introductionmentioning
confidence: 99%
“…However, neither the Open Journal of Physical Chemistry mechanism of the anticonvulsant activities nor the molecular target(s) of these active enaminones have been fully determined or known. There is some evidence that the anticonvulsant activities of these enaminones appear to act through two modes of action: inhibition of sodium channels and via a GAB Aergic pathway [7] [8]. Recent electrophysiology studies have shown that some of a group of newly synthesized 6 Hz active anticonvulsant fluorinated N-benzamide enaminone analogs exhibit inhibition of Na v channels [14].…”
Section: Introductionmentioning
confidence: 99%
“…In our previous studies, we found the enaminone system to be an excellent pharmacophore for anticonvulsant active analogs [ 6 , 7 , 8 , 9 , 10 , 11 , 12 ]. Enaminones, the enamine of β-dicarbonyl compounds, are well known as versatile building blocks for the synthesis of various heterocycles [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, halogenated derivatives of N ‐substituted‐4‐aminobenzenesulfonamides, as well as triazine sulfa drug derivatives, have shown remarkable activity towards carbonic anhydrase isozymes1,2 and anticancer activity3 as well. Compounds such as anilino enaminones have found applications as potential anticonvulsant agents, and the fluoro, trifluoromethyl, and trifluoromethoxy derivatives have shown substantially enhanced activity 4. Also, largely prescribed anesthetics such as procaine and benzocaine contain aminoaromatic functionalities.…”
Section: Introductionmentioning
confidence: 99%
“…Compounds such as anilino enaminones have found applications as potential anticonvulsant agents, and the fluoro, trifluoromethyl, and trifluoromethoxy derivatives have shown substantially enhanced activity. [4] Also, largely prescribed anesthetics such as procaine and benzocaine contain aminoaromatic functionalities.…”
Section: Introductionmentioning
confidence: 99%